Sudden unexpected atraumatic arterial dissection-related death after seizures - Vega, Jose L.; Karim, Nurose; Hall, Caroline (Seizure (London, England), 2024)
•In susceptible patients, epileptic seizures may trigger acute atraumatic arterial dissections.•Postconvulsive leukocytoses may be linked to seizure-induced atraumatic aortic dissections.•Chronic hypertension may be a risk factor for atraumatic aortic dissections associated with epileptic seizures.•SUADAS might be a distinct cause of seizure-induced sudden death. To date, it has been assumed that acute seizures which arise in the context of sudden, spontaneous, atraumatic, acute, arterial dissections (SAAADs) are downstream consequences of the dissections driven by syncope or focal brain lesions (FBLs). As this subject has not been formally investigated, likely due to its rarity, we reviewed published case reports (CRs) to examine the veracity of this assumption. We included CR describing patients diagnosed with both acute seizures and arterial dissections in order to ascertain the temporal sequence between acute seizures and typical SAAAD symptoms. In addition, we quantified the frequency with which hypotension, bradycardia, and FBLs are associated with acute seizures in such cases. We found 45 published CRs, six (13.3%) of which involved traumatic arterial dissections and 39 (86.7%) which involved SAAADs. Of the latter, twenty-one (53.8%) described seizures that followed typical SAAAD symptoms (SAFO), and 18 (46.2%) that preceded all such symptoms (SATO). On average, blood pressure and heart rate for both groups exceeded the normal range. Of the CRs that included magnetic resonance imaging (MRI) scans, 8 (100%) SAFO but only 6 (54.5%) SATO patients demonstrated FBLs (p<0.03). A conspicuously large fraction of SATO patients had known epilepsy compared with SAFO patients, (33.3% vs 4.8%; p<0.02). In addition, SATO epilepsy patients’ seizure semiologies frequently resembled their breakthrough seizures (BTS). The most common SAAAD associated with acute seizures was aortic dissection (AoD; 17/45; 37.8%). Nine CRs (20%) described patients who died soon after presentation, seven of which were associated with AoDs, including one epilepsy patient. Six of these seven AoDs occurred in patients who suffered from chronic hypertension (CHTN). All five deaths in the SATO group followed first ever seizures (FES) [four AoDs and one coronary artery dissection (CoAD)]. Acute seizures arising in the context of SAAADs are not necessarily associated with hypotension or FBLs, and frequently appear to precede the associated dissections. These results suggest that seizures could act as triggers for SAAADs. In addition, sudden unexpected atraumatic acute arterial dissection-related death after seizure (SUADAS) might be a distinct cause of sudden death in epilepsy patients.